Assessment of Food Supplement Consumption in Polish Population of Adults - Stoś, Katarzyna; Woźniak, Agnieszka; Rychlik, Ewa; Ziółkowska, Izabela; Głowala, Aneta; Ołtarzewski, Maciej (Frontiers in Nutrition, 2021)
Introduction: In recent years, there has been a great interest in food supplements. However the use of food supplements can be associated with the risk of excessive intake of vitamins or minerals which may have adverse health effects. Objective: Assessment of food supplement consumption in the adult population in Poland. Material and methods: The study was conducted on 1831 adults (913 men, 918 women) from which 178 (59 men, 119 women) food suplement users were selected.The consumption of food supplements were assessed by the 24-hour recall repeated two times and the food propensity questionnaire (FPQ). Results: 10% of the subjects consumed food supplements during the 12 months prior to the study (6% of men, 13% of women) and among users 68% (79% of men and 88% women) in the day before the survey. Most respondents (44%) used vitamin supplements during the year. More men than women (27% vs 11%, p=0,0059) used mineral supplements while more women than men used vitamin and mineral supplements (31% vs 8%, p=0,0008). The most frequently supplemented vitamins were: B6 (58%), C (53%) and D (47%) and minerals were: magnesium (43%), zinc (34%) and iron (29%). More women than men supplemented vitamin B6 (71% vs 40%, p=0.0012), vitamin D (54% vs 36%, p=0.0061) and magnesium (49% vs 34%, p=0,0075). Intake of riboflavin, pantothenic acid and manganese were higher in the group of men (respectively: 3.3±6.0 vs 1.4±0.3, p=0.0329; 9.4±5.6 vs 6.1±2.0, p=0.0357; 2.2±0.9 vs 1.3±0.6, p=0.0080) but intake of vitamin D was higher in the group of women (15.7±20.4 vs 33.1±26.4, p=0.0085). In many cases, the intake of vitamins and minerals from food supplements covered the dietary reference values for these nutrients in 100%. In some persons the intake of biotin, vitamin B12, C, B6, riboflavin, niacin was higher than the reference values several dozen times. The intake of vitamins and minerals exceed UL in a few cases relating to vitamin B6 and magnesium. Conclusions: A mirority of adults in Poland used food supplements. However, those products were a significant source of vitamins and minerals. Intake of vitamins and minerals from food supplements should be monitored.